Singaporean's attitudes on food hygiene. - Fong, Soke Yeen. (2008)
This study assessed Singaporeans' level of food safety knowledge in areas of cross contamination, general food safety knowledge, personal hygiene, sanitation, food storage and time and temperature. The impact of demographic factors on the level of food safety knowledge was also examined. In addition, recommendations to improve the level of food safety knowledge was suggested.